Ruby developer's guide - Feldt, Robert; Johnson, Lyle.; Neumann, Michael, 1980- (Rockland, MA : Syngress Pub., 2002)
An expert guide to Ruby, a popular new Object-Oriented Programming Language Ruby is quickly becoming a favourite among developers who need a simple, straight forward, portable programming language. Ruby is ideal for quick and easy object-oriented programming such as processing text files or performing system management. Having been compared with other programming languages such as Perl, Python, PCL, Java, Eiffel, and C++; Ruby is popular because of its straight forward syntax and transparent semantics. Using step-by-step examples and real world applications, the Ruby Developer's Guide is designed for programmers and developer's looking to embrace the object-oriented features and functionality of this robust programming language. Readers will learn how to develop, implement, organize and deploy applications using Ruby. Ruby is currently experiencing a rapid rise in popularity in the object-oriented programming community Readers receive up-to-the minute links, white papers, and analysis for two years at solutions@syngress.com Comes with a wallet-sized CD containing a printable HTML version of the book, all of the source code examples and demos of popular Ruby third-party programming tools and applications.
Booting Ruby -- GUI toolkits for Ruby -- Accessing databases with Ruby -- XML and Ruby -- Web services and distributed Ruby -- WWW and networking with Ruby -- Miscellaneous libraries and tools -- Profiling and performance tuning -- Parser generators -- Extending and embedding Ruby.
Includes bibliographical references and index.
Keywords: Object-oriented programming (Computer Science).; Ruby (Computer program language); Electronic books